A molecular dynamics simulation study of thermal conductivity anisotropy in β-octahydro-1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazocine (β-HMX). (23rd January 2020) - Chitsazi, Rezvan; Kroonblawd, Matthew P; Pereverzev, Andrey; Sewell, Tommy
Abstract: Molecular dynamics (MD) simulations were used to predict the thermal conductivity of β -octahydro-1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazocine ( β -HMX) along directions normal to the (011), (110), and (010) crystal planes. These directions were selected based on the measured morphological importance of the corresponding crystal surfaces. A reverse non-equilibrium MD approach was used wherein a constant heat flux is imposed along a prescribed direction and the resulting steady-state temperature gradient determined. The coefficient of thermal conductivity λ is the quotient of heat flux and temperature gradient (i.e. Fourier's law). Finite-size effects and sensitivity to imposed heat flux were investigated. The results reveal a modest dependence of the conductivity on crystal orientation, significant finite-size effects, and low sensitivity to imposed flux so long as the Fourier's law analysis is limited to the spatial interval in the simulation cell for which the temperature gradient is constant. Infinite-length thermal conductivities were estimated by linear regression of λ −1 ( L ) versus reciprocal cell length L −1 for each direction. The predicted values are systematically larger, but within a factor of two, than most published experimental determinations, the latter of which were obtained for pressed-powder or composite samples rather than oriented single crystals.